Porosity estimation in deep-water slope-channel system using seismic inversion model: A case study from the Nile Delta Basin, Egypt - EID, Ramy; EL-ANBAAWY, Mohamed; EL-TEHIWY, Adel (Contributions to Geophysics and Geodesy, 2023)
The area of study is a Pliocene gas field, located in the Eastern portion of the West Nile Delta Deep Marine Concession (WDDM) offshore Egypt. The primary aim of this study is to establish a methodology for direct porosity estimate from 3D post-stack inversion (Zp) and assess its reliability. Porosity estimation from seismic inversion is a commonly used technique in geophysics to predict subsurface porosity from seismic data. Seismic inversion is the process of converting seismic reflection data into a quantitative representation of subsurface properties. Seismic inversion methods aim to relate the seismic response (amplitude, phase, frequency content) to rock properties such as porosity. The inversion process typically involves the following steps: Acoustic impedance inversion from seismic data is a widely utilized technique in reservoir characterization. In cases where well penetrations are limited, the resulting impedance section can be employed to predict reservoir parameters, including porosity. However, the relationship between acoustic impedance (AI) and porosity is influenced by the lithofacies and requires geological interpretation. To construct a porosity map and porosity static model, a comprehensive methodology was developed, capitalizing on the expected porosity volumes. By applying cut-offs to shear and acoustic impedance logs, categorical facies or fluid classes were established. The mean porosity for each lithofacies category is determined from the porosity logs of the wells under study. The inverted porosity model is validated against well log data or other independent measurements like core porosity to assess its accuracy and reliability. If necessary, additional adjustments or calibration may be performed to improve the porosity estimation. Subsequently, a final trend porosity volume was generated to estimate the porosity in areas distant from the study wells by establishing a correlation between average porosity values and acoustic impedance. This process of creating a porosity map will significantly mitigate drilling uncertainties going forward.